Challenges of the green building construction industry in Malaysia - Aliou, Mariam (Kulliyyah of Architecture and Environmental Design, International Islamic University Malaysia, 2015)
Society has an obligation to the environment, which is deteriorating as a result of irresponsible human activity. In the realm of the built environment, that obligation manifests itself through green building construction. However, reluctance of professionals, especially contractors, in the green building construction industry to embrace green building practices and the high level of energy consumption in buildings are prevalent problems in Malaysia. This study has explored the inherent bureaucratic, technical, and social factors contributing to these problems. This was done through extensive literature review, case studies of green certified buildings in Malaysia, comparative study of GBI, Green Mark and LEED, structured interviews with the versatile professionals in the industry, and in-depth interviews with experienced industry professionals and policy makers. The theoretical framework was based on the major factors affecting green building construction, which are lack of education and awareness, lack of attractive incentives, reluctance to embrace change, insufficient finances, ineffective policies, and lack of resources. This study has identified the prevalent challenges impeding the advancement of green building construction through having investigated the technical and bureaucratic aspects of the green building construction industry, having examined the inherent social factors that impact the green building construction industry, and having identified the shortcomings of GBI. Through analysis of the qualitative field research findings and comparative analysis of GBI, Green Mark and LEED, this study has answered the research questions of what the disadvantages of the green building construction industry are, what actions and incentives it takes to motivate those in the industry to adopt green building construction, and what strategies GBI can apply from Green Mark and LEED, which are applicable in a Malaysian context. The study has discovered that the factors affecting the green building construction industry are as follow: perceived inefficiency of GBI, low level of knowledge and expertise, overlapping and lax bureaucracy, and a lack of attractive incentives. These findings are used to recommend countermeasures to these challenges for the purpose of optimizing the potential of the green building construction industry in Malaysia.